2014
DOI: 10.1111/his.12460
|View full text |Cite
|
Sign up to set email alerts
|

Differential SALL4 immunoexpression in malignant rhabdoid tumours and epithelioid sarcomas

Abstract: Despite moderate sensitivity, SALL4 expression may aid in distinguishing MRTs from ESs. CD34 was found to have questionable utility in making such distinctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
(115 reference statements)
6
17
0
3
Order By: Relevance
“…Loss of E-cadherin [24] associated with variable loss of pancytokeratin [16,24] has been reported in dedifferentiated carcinoma of uterus and other organs. Expression of SALL4, which was observed in our case, has been recently reported in malignant rhabdoid tumors as well [28]. To assess the possibility of SMARCA4 loss as a secondary event in the setting of microsatellite instability as seen in a subset of microsatellite instability colorectal cancer [23], we stained the SMARCA4-deficient case with the 4 mismatch repair proteins proteins; all showed intact expression.…”
Section: Discussionsupporting
confidence: 57%
“…Loss of E-cadherin [24] associated with variable loss of pancytokeratin [16,24] has been reported in dedifferentiated carcinoma of uterus and other organs. Expression of SALL4, which was observed in our case, has been recently reported in malignant rhabdoid tumors as well [28]. To assess the possibility of SMARCA4 loss as a secondary event in the setting of microsatellite instability as seen in a subset of microsatellite instability colorectal cancer [23], we stained the SMARCA4-deficient case with the 4 mismatch repair proteins proteins; all showed intact expression.…”
Section: Discussionsupporting
confidence: 57%
“…[18][19][20][21][22][23] In the present study, CD34 immunoreactivity was found in 12 of the 38 rhabdoid tumor cases (31%), and the previously reported immunoreactive ratio was 60%. 23 Therefore, CD34 may not be useful as a differential diagnostic marker. On the other hand, the immunoreactive ratios for ERG, SALL4, or GPC3 in the current reclassified rhabdoid tumor cases, including our previously reported cases, were 10%, 61%, and 59%, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…At present, immunoreactivity for CD34 is generally accepted as a differential marker; approximately half of all epithelioid sarcoma cases are positive for CD34, whereas malignant rhabdoid tumor cases scarcely reveal immunoreactivity for this marker. [18][19][20][21][22][23] In the present study, CD34 immunoreactivity was found in 12 of the 38 rhabdoid tumor cases (31%), and the previously reported immunoreactive ratio was 60%. 23 Therefore, CD34 may not be useful as a differential diagnostic marker.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In yolk sac tumors and primary extragonadal germ cell tumors, one study reported that the circulating tumor cells are detectable by anti-SALL4 antibody in peripheral blood samples, making this protein a more sensitive marker than α-fetoprotein and glypican-3 107 . In addition, SALL4 is expressed in a majority of malignant rhabdoid tumors (MRTs) 20108109110111 but rarely expressed in epithelioid sarcomas. Therefore, SALL4 immunoexpression may be a useful diagnostic tool to distinguish epitheloid sarcoma from malignant rhabdoid tumor.…”
Section: Sall4 In Cancersmentioning
confidence: 99%